Rain rate distributions for microwave link design based on long term measurement in Malaysia - Islam, Md. Rafiqul; Alam, Md. Moktarul; Lwas, Ali Kodhim (2017)
Attenuation due to rain is an important constraint in microwave radio link design especially at frequencies above 10 GHz. It restricts the path length of radio communication systems and limits the use of higher frequencies for line-of-sight microwave links and satellite communications. In order to predict the attenuation due to rain accurately rainfall intensity is required with 1-minute integration time. Rainfall is a meteorological phenomenon with complex structure due to its variability in space, duration and occurrence frequency, particularly in tropical and equatorial regions. Since, the statistical distribution of rain attenuation is obtained from the rain rate distribution for the region considered, it should be noted that the accuracy of the rain rate measurement affects the accuracy of the attenuation estimation. This paper presents rain intensity with 1-minute integration time measured for 6 years in Malaysia, it’s distribution, comparison with other prediction models and impact on high frequency microwave links.